2023
DOI: 10.1002/lno.12315
|View full text |Cite
|
Sign up to set email alerts
|

Tracing basal resource use across sea‐ice, pelagic, and benthic habitats in the early Arctic spring food web with essential amino acid carbon isotopes

Abstract: A rapidly warming Arctic Ocean and associated sea‐ice decline is resulting in changing sea‐ice protist communities, affecting productivity of under‐ice, pelagic, and benthic fauna. Quantifying such effects is hampered by a lack of biomarkers suitable for tracing specific basal resources (primary producers and microorganisms) through food webs. We investigate the potential of δ13C values of essential amino acids (EAAs) (δ13CEAA values) to estimate the proportional use of diverse basal resources by organisms fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…2b) that had exclusively pelagic signatures at the time of sampling. Given these are the only taxa lacking in iPOC signatures entirely, which contrasts other studies 22,23,38 , this is likely the result of rapid HBI turnover rates in zooplankton and sample timing, which does not rule out the utilization of iPOC for these zooplankton species or an exclusive reliance on phytoplankton. Accordingly, we provide the first direct demonstration of the persistent role sea-ice primary production plays in supporting the energy requirements throughout a majority of the marine and coastal food webs across the Arctic, extending beyond the narrow springtime window of initial production (Fig.…”
Section: Increased Importance Of Springtime Sea-ice Carbonmentioning
confidence: 67%
See 2 more Smart Citations
“…2b) that had exclusively pelagic signatures at the time of sampling. Given these are the only taxa lacking in iPOC signatures entirely, which contrasts other studies 22,23,38 , this is likely the result of rapid HBI turnover rates in zooplankton and sample timing, which does not rule out the utilization of iPOC for these zooplankton species or an exclusive reliance on phytoplankton. Accordingly, we provide the first direct demonstration of the persistent role sea-ice primary production plays in supporting the energy requirements throughout a majority of the marine and coastal food webs across the Arctic, extending beyond the narrow springtime window of initial production (Fig.…”
Section: Increased Importance Of Springtime Sea-ice Carbonmentioning
confidence: 67%
“…It has also been suggested that bacteria may consume greater proportions of this highly degraded pelagic detritus than benthic macrofauna 22,59 .…”
Section: Increased Importance Of Springtime Sea-ice Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of multiple independent trophic biomarkers such as essential amino acid carbon isotopic fingerprints may be used to constrain assumptions about the susceptibility of trophic biomarkers to these variations. For example, the general patterns in the importance of sympagic and pelagic diatoms and dinoflagellates for June/July A. glacialis was confirmed in a study using the 13 C signature of essential amino acids and demonstrated that the under‐ice diatom, Melosira arctica , could have significantly contributed to the diatom‐associated fatty acid signal (Vane et al 2023).…”
Section: Discussionmentioning
confidence: 91%
“…Sampling and isolating primary producers in the wild remains challenging, especially for bacteria, whose fingerprinting is typically derived from lab cultures. An alternative approach involves sampling primary consumers, which integrate basal fingerprinting over time and provide a site-specific baseline (Skinner et al, 2021;Vane et al, 2023). However, primary consumers themselves may exhibit overlaps, particularly for brown and blue consumers that derive carbon from bacteria, fungi, and plant, and bacteria, algae, and plant, respectively.…”
Section: Introductionmentioning
confidence: 99%